Comparative study on the evolution of polar compound composition of four common vegetable oils during different oxidation processes. (July 2020) - Chen, Jia; Zhang, Lingyan; Li, Qi; Wang, Mengzhu; Dong, Yaoyao; Yu, Xiuzhu
Abstract: Deterioration of edible oil greatly affects its sensory attributes and nutritional quality. The aim of this work was to compare the influence of oil type on the polar compound composition of vegetable oils (peanut, rapeseed, soybean, and linseed oils) during different oxidation processes (Schaal oven test, room temperature storage, and traditional Chinese cooking). High-performance size exclusion chromatography (HPSEC) was used to determine the polar compound composition of oil. Results showed that the effect of oil type was relatively more significant than that of treatment. For the oil type, oxidized triglyceride monomers (OxTG), triglyceride dimers (TGD), and triglyceride oligomers in linseed oil were higher than in other oils under the same condition. This finding could be attributed to the high percentage of polyunsaturated fatty acids in oils, leading to a high level of oxidized and polymeric triglycerides. In terms of treatment, the ratio of OxTG and TGD changed significantly during the Schaal oven test and traditional Chinese cooking, which could be ascribed to the oxidation temperature of treatment ( P  < 0.05). These findings indicated that the influence of oil deterioration on the oxidized and polymeric products was relatively more significant than that of others during oxidation processes. Highlights: The highlights of this paper are as following: The comparison of polar compound composition of oils during storage and processing. The selection of OxTG, TGD and TGO as indicators of quality evaluation of oils. OxTG that formed was higher in oils during oxidation processes. The TGP contents in oils were no higher than 10% during oxidation processes.